Effect of Cerebral Dominance on Postoperative Pain - Mohammed Kado; Yeşim Çokay Abut; Veysel Erden (İstanbul Medical Journal, 2024)
Introduction: In this study, we aimed to determine the functional dominance of the right and left hemispheres of the operated patients and the effectiveness of postoperative pain therapy when the patients underwent surgery on the same or different sides with the dominant hemisphere. Methods: The patients were given a Miles test for the dominant eye in the preoperative period and were instructed while the key was in front of the patient to take the key and open the door to determine the dominant hand. For the dominant foot, the patient was given the command of “move your foot” in a calm environment and accepted as the foot that he carried the dominant foot. After routine spinal anesthesia and elective knee arthroplasty surgery, patients underwent Patient Controlled Analgesia device, 24th hour Numeric Rating Scale (NRS) scores, and the amount of total applied analgesic and additional analgesic were recorded. Results: When the clinical characteristics of the patients were examined, there were 38 patients on the right side of the dominant eye, 34 on the left side, 67 on the right hand dominant side, 5 on the left side, 49 on the right foot dominant side, and 23 on the left side. The NRS score on the surgical side was compared with the dominant foot, dominant eye, and dominant hand. There was no statistically significant difference between the NRS pain scale and other variables except those opposed to the dominant eye (p>0.05). The NRS pain scale median (median: 3.0) was found to be significantly lower in patients who were operated on the same side as the dominant eye (p=0.016). Conclusion: According to the results of our study, the NRS score was not changed in patients operated on the same side of the dominant foot and hand, whereas the NRS score was lower in patients operated on the same side with the dominant eye.